Autoradiographic and histopathological studies of boric acid-mediated BNCT in hepatic VX2 tumor-bearing rabbits: Specific boron retention and damage in tumor and tumor vessels. (December 2015) - Yang, C.H.; Lin, Y.T.; Hung, Y.H.; Liao, J.W.; Peir, J.J.; Liu, H.M.; Lin, Y.L.; Liu, Y.M.; Chen, Y.W.; Chuang, K.S.; Chou, F.I.
Abstract: Hepatoma is a malignant tumor that responds poorly to conventional therapies. Boron neutron capture therapy (BNCT) may provide a better way for hepatoma therapy. In this research, 10 B-enriched boric acid (BA, 99% 10 B) was used as the boron drug. A multifocal hepatic VX2 tumor-bearing rabbit model was used to study the mechanisms of BA-mediated BNCT. Autoradiography demonstrated that BA was selectively targeted to tumors and tumor vessels. Histopathological examination revealed the radiation damage to tumor-bearing liver was concentrated in the tumor regions during BNCT treatment. The selective killing of tumor cells and the destruction of the blood vessels in tumor masses may be responsible for the success of BA-mediated BNCT for liver tumors. Highlights: 10 B-enriched boric acid (BA) was used for BNCT in hepatic tumor-bearing rabbits. BA was selectively targeted to tumors and tumor blood vessels. Radiation damage was concentrated in tumor regions during BA-mediated BNCT. Selective destruction to tumor regions led to the success of BA-mediated BNCT.